STRATEGI KOMUNIKASI KEMENTERIAN KOMUNIKASI DAN INFORMATIKA DALAM KAMPANYE NASIONAL PENURUNAN PREVALENSI STUTNING - Mulyadi, Ahmad; Naryoso, Agus; Yuliyanto, Muchamad; Surayya Ulfa, Nurist (Interaksi Online, 2022)
Stunting is a condition of growth failure in children due to chronic malnutrition and repeated infections in the First 1000 Days of Life (HPK). One of the causes of the high prevalence of stunting in Indonesia is due to public awareness and ignorance about stunting. The government through the Ministry of Communications and Informatics has developed a campaign communication strategy to achieve the target of reducing stunting prevalence to reach 14% in 2024. This study aims to describe and analyze the communication strategy of the national campaign to reduce stunting prevalence carried out by the Ministry of Communications and Informatics. This research uses a qualitative descriptive approach with a case study method. Data collection techniques were carried out through in-depth interviews, documentation, and observation. The concepts used are the concept of PR Campaign Planning, Public Information Model, and Multi Step Flow Communication Model. The results showed that the communication strategy of the Ministry of Communications and Informatics in the stunting campaign has gone through stages that are in accordance with the concept of PR campaign planning, starting from situation analysis, setting goals, public, messages, strategies and tactics, time scale and resources, as well as evaluation and review. The purpose of the stunting campaign is to increase public awareness and understanding of stunting. For this reason, the Ministry of Communications and Informatics disseminates information that is informative, educative, and persuasive through multi-channel communication (mass media, outdoor media, online media, social media, and direct media) with a focus on targeting young women and mothers of productive age. The implementation of the campaign is carried out under the coordinator of the Sub-directorate of Health Information and Communication by involving a third party to execute the program. The evaluation was carried out to see the campaign's achievements related to the reach and understanding of the community. As well as a review carried out to identify strategic changes that need to be made for the following year's campaign